Characterisation of the Neoarchean Fortescue Group Stratigraphy – Integrated downhole geochemical mineralogical correlation from new diamond drilling. Issue 1 (1st December 2019) - Stromberg, Jessica; Spinks, Sam; Pearce, Mark
Summary: The flood basalts and gold-bearing basal sediments of the 2775-2629 Ma Fortescue Group unconformably overlie the Mesoarchean West Pilbara Superterrane to the south of Karratha, Western Australia. Fresh exposures of the sedimentary units are lacking and their geochemical, mineralogical composition and sequence stratigraphy under cover are largely unknown. This research outlines the results of integrated downhole geochemistry and hyperspectral mineralogy of two new diamond drill holes, 4 km apart, which intersect the Fortescue group stratigraphy into the Mesoarchean Pilbara basement. This has been combined with trace element geochemistry, and high-resolution XRF mapping of representative samples provide micro-structural insights and in-situ geochemistry with textural context. The lithostratigraphy of the holes was defined using automated geochemical logging and tessellation methods, which provide objective classification of geologic units based on geochemistry and mineralogy. Individual basalt flows within the Kylena Formation can be correlated across holes based on chlorite content and geochemistry, and a chromium-rich geochemical marker horizon has been identified at the top of the siliciclastic Hardey Formation. The granitic basement rocks show evidence of significant fluid flow are interpreted to be a southern extension of the Maitland River Supersuite, consistent with regional geophysical anomalies that show a continuous gravity low. This dataset provides an unprecedented view into the Fortescue Group stratigraphy and its geochemistry. Correlation of this dataset with previous drilling provides insights into the regional tectonic and depositional history of the basin. The depth to basement increases from 650 m to >2200 m over ~12km N-S and the thickness of the clastic sedimentary basal Hardey Formation increases from ~150 m to 1050 m respectively. This indicates significant variation in the geometry of the basement during the deposition of the basal Hardey Formation, which was likely influenced by synsedimentary rifting. This has implications on the distribution of potential gold-bearing conglomerate facies unconformably overlying the basement, and in the Hardey Formation.